Principles of properness in partnership relationships with MSME business actors - Yeni Triana; Yelia Nathassa Winstar (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
The purpose of this study was to analyze the principle of propriety of business actors in establishing partnerships in Umkm Tugu Keris, Pelayaran District, Pekanbaru City where in the implementation of the agreement it was preceded by an agreement by both parties as a guide to reach an agreement that was not carried out by the parties in accordance with what was stated. has been stated to have been agreed upon in the contents of the agreement. The research method used is sociological law with a descriptive approach. The population and samples are business actors, government agencies, consumers. Oral interview method to find information as data if for this research. The analysis technique uses qualitatively analyzed data which is then expressed in qualitative descriptive language and sentences. The results of the research on the principle of propriety in partnership relationships still need to be considered for changes in the behavior of UMK business actors, in relation to establishing this collaboration it is expected to be even better, namely providing comfort and satisfaction for visitors as customers in enjoying every merchandise offered by business actors at Tugu